TANTANGAN MENJAGA NILAI KETUHANAN DI ERA AI: PERSPEKTIF MAHASISWA BARU INFORMATIKA UNIVERSITAS JEMBER - Pratama, Mohamad Febri; Mrr Ratna Endang; Nadia Hayfa Kenzabrina; Tantya Cici Ramadani; Zahra Salsabila Purida; Yudha Rendra Dinata (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The development of artificial intelligence (AI) has brought about significant changes in the way students think, learn, and interact. This study aims to explore how students in the Informatics Study Program at the University of Jember understand and uphold divine values ​​amidst the increasing use of AI. Using a descriptive quantitative method through a survey of 30 new Informatics Study Program students, the results show that the majority of students recognize the importance of divine values ​​as ethical guidelines in the use of AI. However, some face a dilemma between technological efficiency and spiritual integrity, particularly regarding academic integrity and the potential for dependency that undermines religious reflection. Nevertheless, a new awareness is emerging that AI should be used as a tool that supports human values. This study emphasizes the need for a digital literacy curriculum that integrates technical skills with moral and spiritual values ​​to ensure the ethical use of AI and shape students' character in the digital era.